Goniothalamus flagellistylus Tagane & V. S. Dang (Annonaceae), a new species from Mt. Hon Ba, Vietnam - Tagane, Shuichiro (PhytoKeys, 2015)
Abstract. A new species, Goniothalamus flagellistylus Tagane & V. S. Dang, sp. nov. from Hon Ba Nature Reserve in Khanh Hoa Province, South Vietnam is described and illustrated. This species is most similar to Goniothalamus tortilipetalus M.R.Hend., but distinct in having 308–336 stamens (vs. ca. 170–260) and ca.120 carpels (vs. ca. 50–100) per flower, and Stigma and pseudostyles ca.8.5 mm (vs. 4–4.5 mm) long.